2016
DOI: 10.3389/fimmu.2016.00468
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Exacerbate Lyme Borreliosis in TLR2-Deficient Mice

Abstract: Infection of humans with the spirochete, Borrelia burgdorferi, causes Lyme borreliosis and can lead to clinical manifestations such as arthritis, carditis, and neurological conditions. Experimental infection of mice recapitulates many of these symptoms and serves as a model system for the investigation of disease pathogenesis and immunity. Innate immunity is known to drive the development of Lyme arthritis and carditis, but the mechanisms driving this response remain unclear. Innate immune cells recognize B. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…These T cells, in turn, enhanced mononuclear cell migration via the increased release of other inflammatory factors . A recent study in C3H/HeN mice showed that this increase may be attributed to CD8 T‐cell activation of synoviocytes . Moreover, transcripts for the IFN‐inducible gene IFN‐γ‐induced GTPase were elevated .…”
Section: The Role Of the Innate Immune System During The Early Stagesmentioning
confidence: 98%
See 3 more Smart Citations
“…These T cells, in turn, enhanced mononuclear cell migration via the increased release of other inflammatory factors . A recent study in C3H/HeN mice showed that this increase may be attributed to CD8 T‐cell activation of synoviocytes . Moreover, transcripts for the IFN‐inducible gene IFN‐γ‐induced GTPase were elevated .…”
Section: The Role Of the Innate Immune System During The Early Stagesmentioning
confidence: 98%
“…The number of T cells attracted to the joint tissue was enhanced, possibly through augmented production of T‐cell chemokines CXCL9 and CXCL10. These T cells, in turn, enhanced mononuclear cell migration via the increased release of other inflammatory factors . A recent study in C3H/HeN mice showed that this increase may be attributed to CD8 T‐cell activation of synoviocytes .…”
Section: The Role Of the Innate Immune System During The Early Stagesmentioning
confidence: 98%
See 2 more Smart Citations
“…TLR signaling leads to increased production of numerous cytokines that induce pro-inflammatory responses (25, 47). Interestingly, TLR-deficient mice had exacerbated inflammation and increased spirochetal burdens, both of which were attenuated by impairing T cell responses (70). As a bodily response to the vast amounts of pro-inflammatory cytokines produced upon spirochetal lipoprotein presence, monocytes have also been seen to produce IL-10 upon being presented with B. burgdorferi lipoproteins (71–75).…”
Section: Modulatory Effects Of Spirochetal Lipoproteins Related To Acmentioning
confidence: 99%